2014
DOI: 10.1007/s12034-014-0695-9
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Optical and Photoluminescence Study of Nanocrystalline SnO2 Thin Films Deposited by Spray Pyrolysis

Abstract: Undoped SnO 2 thin films prepared by spray pyrolysis method reveal polycrystalline nature with prominent peaks along (110), (101) and (211) planes. All the films are nanocrystalline with particle size lying in the range of 3⋅14-8⋅6 nm calculated by DS formula. Orientation along plane (200) decreases continuously as molar concentration of SnO 2 increases. Dislocation density along plane (110) also decreases as molar concentration increases except 0⋅4 M SnO 2 thin film. Scanning electron microscopy image of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…Because, the UV shift can be attributed to the increased crystallinity and a higher carrier concentration [51]. These values are like to the results reported by previous reports [19,52,53].…”
Section: Photoluminescence (Pl) Studiessupporting
confidence: 90%
“…Because, the UV shift can be attributed to the increased crystallinity and a higher carrier concentration [51]. These values are like to the results reported by previous reports [19,52,53].…”
Section: Photoluminescence (Pl) Studiessupporting
confidence: 90%
“…The blue and green emissions at 485 nm and 527 nm are probably related to the existence of various intrinsic defects in the NiSnO 3 crystal lattice. Akhilesh et al prepared undoped SnO 2 thin films by spray pyrolysis method at different concentration[21]. They have related the origin of both the peaks to defects or to defect levels associated with oxygen vacancies or X-ray diffraction spectra.…”
mentioning
confidence: 99%
“…It can be given for example spray pyrolysis (Yuwono et al, 2017), spin coating (Kadhim et al, 2017), pulsed laser deposition (Martin et al, 2004), dip coating (Carvalho et al, 2012) and sputtering (Zhu et al, 2017) methods. Among them, it was found that spray pyrolysis method have interesting properties such as simple and inexpensive experimental setup, reproducibility, easily adding of doping materials, preparing thin films with high quality (Tripathi and Shukla, 2014). The properties of TCOs thin films have been fabricated by spray can be changed with substrate temperature, spray time, spray flow rate, nozzle-substrate distance, precursors and solvents etc.…”
Section: Introductionmentioning
confidence: 99%